Analysis of the reliability of an Islamic communication instrument based on the conditions of authentic hadith - Md Sharipp, Muhammad Taufik; Suyurno, S Salahudin; Ridzuan, Abdul Rauf; Aini, Zulkefli (Faculty of Communication & Media Studies, 2025)
This article discusses the development and reliability assessment of an Islamic communication instrument based on the five conditions of authentic hadith, namely connected sanad, justice of the narrator, perfect dhabṭ, free from syādh, and free from ‘illah. The need for this study arises from the challenge of disseminating religious information in the digital era, which is often not carefully filtered and risks containing inauthentic elements. The study employed a quantitative approach through a questionnaire developed on the principles of hadith sciences and distributed to 151 certified preachers in the state of Melaka. Data were analysed using Cronbach’s Alpha to measure reliability, and Confirmatory Factor Analysis (CFA) to evaluate construct validity. The findings indicate that the Cronbach’s Alpha values for all constructs are at a high level (α=0.827 to α=0.913), while the KMO value (.868) and Bartlett’s Test (p<.001) confirmed the suitability of the data for factor analysis. In addition, the AVE and Composite Reliability (CR) values also met the required standards, us affirming the instrument’s convergent validity. These results demonstrate that the instrument developed is valid and reliable for assessing the quality of Islamic communication and has the potential to serve as a basis for filtering religious information, strengthening the credibility of preachers, and ensuring the accuracy of religious messages in contemporary society.